Analisis Kontrastif Fonologi Bahasa Arab dan Bahasa Indonesia: Perbandingan Vokal dan Konsonan - Muid, Faruq Abdul (Bilingua, 2025)
The study explored the impact of differences in vocal and consonant systems between Arabic and Indonesian languages on the pronunciation and understanding of native speakers of the two languages. The research uses descriptive qualitative methods with data collection techniques such as in-depth interviews, participatory observations, and document analysis. The study aims to study the effectiveness of learning media innovation in improving Arabic vocabulary skills among students. The study involved 30 students and 5 teachers. The learning media developed includes mobile apps, educational games, and animated videos designed to make the learning process more interactive and exciting. Thematic analysis of qualitative data shows that interaction, visualization, and personalization of learning media are key factors affecting learning effectiveness. Studies have shown that Indonesian Arabic students often have difficulties in distinguishing and pronouncing long and short vocals, as well as Arabic-typical consonants, which can lead to misunderstandings in communication. On the contrary, Arabic speakers who are learning Indonesia have found a more adaptable consonant and vocal system, although regional variations in pronunciation need to be taken into account.